2000
DOI: 10.1161/01.hyp.35.5.1173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sleep Deprivation on Neural Circulatory Control

Abstract: Abstract-Effects of sleep deprivation on neural cardiovascular control may have important clinical implications. We tested the hypothesis that sleep deprivation increases heart rate, blood pressure, and sympathetic activity and potentiates their responses to stressful stimuli. We studied 8 healthy subjects (aged 40Ϯ5 years, 6 men and 2 women). Blood pressure, heart rate, forearm vascular resistance, and muscle sympathetic nerve activity were measured at rest and during 4 stressors (sustained handgrip, maximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
197
4
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(219 citation statements)
references
References 23 publications
17
197
4
1
Order By: Relevance
“…Inadequate sleep may also have consequences for circulatory control that, in the absence of measurements of sleep quality, could be misinterpreted as changes secondary to morning fluctuations in cardiovascular physiology. 40,41 Finally, the use of nitroglycerin-induced dilation as an internal control makes more robust our findings of a selective impairment of FMD but not NFMD.…”
Section: Discussionmentioning
confidence: 67%
“…Inadequate sleep may also have consequences for circulatory control that, in the absence of measurements of sleep quality, could be misinterpreted as changes secondary to morning fluctuations in cardiovascular physiology. 40,41 Finally, the use of nitroglycerin-induced dilation as an internal control makes more robust our findings of a selective impairment of FMD but not NFMD.…”
Section: Discussionmentioning
confidence: 67%
“…11,2741,42 Alcoholic subjects who have a night of insufficient sleep may be particularly vulnerable to increases of blood pressure and heart rate in the morning. 11,12 Cardiovascular events are known to occur more frequently from early morning to noon, 14 and longitudinal studies have found that autonomic dysregulation is related to greater risk of cardiovascular disease. 43 …”
Section: Irwin and Ziegler Sleep Deprivation And Sympathetic Activatimentioning
confidence: 99%
“…Loss of sleep induces elevations in circulating levels of epinephrine and norepinephrine, 9,10 with attendant increases of blood pressure and heart rate the next day. 11,12 In addition, habitual sleep loss and insomnia are markers of subclinical heart disease and are independent predictors of cardiovascular disease risk, particularly in males. 13 Fluctuations in sympathetic activity across the sleep-wake cycle are thought to contribute to the low rates of sudden cardiac death, myocardial infarction, and ischemic stroke during sleep, as well as to their peak incidence at the end of sleep or in the morning after awakening.…”
mentioning
confidence: 99%
“…Short-term sleep deprivation studies suggest that acute sleep deprivation increases BP. 19,20 Furthermore, a relationship between habitual sleep duration and BP 21 and an inverse relation between sleep duration and body mass index (BMI) 22,23 have been demonstrated. Hypertension in short sleepers may then also be favored by the development of obesity.…”
Section: Introductionmentioning
confidence: 99%